UPAYA MENINGKATKAN HASIL BELAJAR SHOOTING FREE THROW BOLA BASKET MELALUI MEDIA AUDIO VISUAL - RESKI AGUNG ADRESTA; OKI CANDRA (PRODI PJKR UNIVERSITAS MUHAMMADIYAH MUARA BUNGO, 2020)
This study aims to determine the increase in learning the ability to shoot free throw in the game of basketball through audio-visual media in high school students 1 Rengat Barat. The study was conducted in the even semester of the 2018/2019 school year. The type of this research is classroom action research, research subjects are students of class X MIPA Rengat Barat Public High School numbering 35 people. This research technique is total sampling. The data analysis technique used in the performance test is the free throw shooting test, while the results of the test are assessed. From the implementation of cycle I and the results there were 17 students who achieved the KKM value (48.57%) and 18 students who had not yet achieved the KKM value (51.43%), followed by the implementation of the second cycle and the results increased with the number of 28 students who achieved the KKM value (80%) and 7 students who have not yet reached the KKM score (20%). Thus it can be concluded that there is an increase in basketball free throw shooting learning through audio-visual media in class X MIPA1 students of SMA Negeri 1 Rengat Barat with an increase of (31.43%).